2014
DOI: 10.1002/jssc.201400276
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic analysis of some drugs employed in erectile dysfunction therapy: Qualitative and quantitative studies using calixarene stationary phase

Abstract: In this study, the effect of change in chromatographic process variables on the retention behavior of four drugs employed in erectile dysfunction therapy on a calixarene stationary phase is described. Three of these drugs are known to treat erectile dysfunction, namely, sildenafil citrate, tadalafil, and apomorphine hydrochloride, and one drug that is used as opioid analgesic, tramadol hydrochloride, which is quiet widely misused to treat premature ejaculation. The results indicate the importance of considerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Tramadol also caused a significant decline in Leydig cells activities (Nna et al, 2017) with a possible reduction in testosterone biosynthesis. Although tramadol has been reported to improve premature ejaculation but adversely affect male reproduction (Hashem et al, 2014;Martyn-St James et al, 2015;Nna et al, 2017), it is structurally different from other members of the opioid family (McMillan, 2018). Leon & Wexler (1973) documented the relationship between heroin addiction and sexual behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Tramadol also caused a significant decline in Leydig cells activities (Nna et al, 2017) with a possible reduction in testosterone biosynthesis. Although tramadol has been reported to improve premature ejaculation but adversely affect male reproduction (Hashem et al, 2014;Martyn-St James et al, 2015;Nna et al, 2017), it is structurally different from other members of the opioid family (McMillan, 2018). Leon & Wexler (1973) documented the relationship between heroin addiction and sexual behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile phase including water without any salt as aqueous part gave bad separation due to tailing of peaks and this is why NaClO 4 is added to aqueous part of the mobile phase. In previous studies, it was found that usage of NaClO 4 as aqueous mobile additive (chaotropic mobile phase additive) led to reduction of retention times and enhancement of separation of basic analytes via decreasing of tailing (Elhenawee et al, 2014;Hashem et al, 2014). The method was validated according to ICH guidelines (Guidance for Industry: ICH 1996) for system suitability, linearity, precision, limits of detection and quantitation, specificity, stability and robustness.…”
Section: Resultsmentioning
confidence: 99%
“…Literature survey revealed that individual determination of the drugs under study was reported extensively. Some papers were reported for simultaneous determination of drugs used in treatment of ED [16][17][18] and some others were reported for simultaneous determination of some antidepressant drugs that can be abused in treatment of PE. 19,20 However, as discussed before, the co-administration of drugs for treatment of ED and PE is possible.…”
Section: Introductionmentioning
confidence: 99%